Interleukin 22 Promotes Blood Pressure Elevation and Endothelial Dysfunction in Angiotensin II–Treated Mice. Issue 10 (3rd October 2017) - Ye, Jing; Ji, Qingwei; Liu, Jianfang; Liu, Ling; Huang, Ying; Shi, Ying; Shi, Lei; Wang, Menglong; Liu, Mengling; Feng, Ying; Jiang, Huimin; Xu, Yao; et al.
Abstract : Background: CD4+ T helper (Th) cells, including Th1, Th2, and Th17 cells, play critical roles in angiotensin II–induced hypertension. Th22 cells, a novel subset of Th cells, take part in cardiovascular diseases by producing IL‐22 (interleukin 22). This study aimed to investigate whether IL‐22 is involved in hypertension. Methods and Results: Th22 cells and IL‐22 levels were detected in angiotensin II–infused mice, and the results showed that Th22 cells and IL‐22 levels significantly increased. To determine the effect of Th22/IL‐22 on blood pressure regulation, angiotensin II–infused mice were treated with recombinant mouse IL‐22, an anti–IL‐22 neutralizing monoclonal antibody, or control. Treatment with recombinant IL‐22 resulted in increased blood pressure, amplified inflammatory responses, and aggravated endothelial dysfunction, whereas the anti–IL‐22 neutralizing monoclonal antibody decreased blood pressure, reduced inflammatory responses, and attenuated endothelial dysfunction. To determine whether the STAT3 (signal transducer and activator of transcription 3) pathway mediates the effect of IL‐22 on blood pressure regulation, the special STAT3 pathway inhibitor S31‐201 was administered to mice treated with recombinant IL‐22. S31‐201 treatment significantly ameliorated the IL‐22 effects of increased blood pressure and endothelial dysfunction. In addition, serum IL‐22 levels were significantly increased in hypertensive patients compared with healthy persons. Correlation analysis showed a positive correlation between IL‐22 levels and blood pressure. Conclusions: IL‐22 amplifies the inflammatory response, induces endothelial dysfunction and promotes blood pressure elevation in angiotensin II–induced hypertensive mice. The STAT3 pathway mediates the effect of IL‐22 on hypertension. Blocking IL‐22 may be a novel therapeutic strategy to prevent and treat hypertension.